2015
DOI: 10.1200/jco.2015.33.28_suppl.86
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new photonumeric scale for acute radiation dermatitis in patients with breast cancer.

Abstract: 86 Background: The Common Terminology Criteria for Adverse Events (CTCAE) is frequently used to grade the severity of acute radiation dermatitis (ARD), but has not been validated despite decades of clinical use. We sought to develop a photonumeric scale to consistently describe ARD in breast cancer patients undergoing radiation (RT). Methods: Patients enrolled on a prospective study that included photographs and quantitative measurements of erythema and hyperpigmentation using colorimetry. 209 photographs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Shumway et al reported the inter-rater reliability of CTCAE scores and showed minimal to moderate agreement among experienced physicians. 23 CTCAE scores showed minimal to moderate correlation with the skin toxicity assessment tools (ie, erythema, burning, itching, pulling, tenderness). 24 In a comprehensive review of the published clinicianreported outcomes of scoring radiation dermatitis, Behroozian et al concluded that there is insufficient evidence to establish a "gold standard" based on CTCAE or any single clinician-reported outcome to assess the radiation dermatitis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Shumway et al reported the inter-rater reliability of CTCAE scores and showed minimal to moderate agreement among experienced physicians. 23 CTCAE scores showed minimal to moderate correlation with the skin toxicity assessment tools (ie, erythema, burning, itching, pulling, tenderness). 24 In a comprehensive review of the published clinicianreported outcomes of scoring radiation dermatitis, Behroozian et al concluded that there is insufficient evidence to establish a "gold standard" based on CTCAE or any single clinician-reported outcome to assess the radiation dermatitis.…”
Section: Introductionmentioning
confidence: 96%
“…However, studies have shown the inconsistencies in these clinician‐reported outcomes in both clinical and research settings. Shumway et al reported the inter‐rater reliability of CTCAE scores and showed minimal to moderate agreement among experienced physicians 23 . CTCAE scores showed minimal to moderate correlation with the skin toxicity assessment tools (ie, erythema, burning, itching, pulling, tenderness) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these clinical evaluations are susceptible to both intra-and interobserver variations. Several studies have highlighted the inconsistencies in clinician-reported outcomes using CTCAE scales, both in clinical and research settings [5,6].…”
Section: Introductionmentioning
confidence: 99%